Buyer-Supplier Relationships: An Examination of How a Small-Medium Supplier can Cooperate Effectively with a Large Buyer - Kritsilis, Nikolaos (2013)
The following research paper examines the possible ways that can ensure that a relationship between a small or medium supplier and a large buyer is going to be successful. The paper starts with an introduction that describes the aims and the objectives of the particular report together with the problem statement. A literature review of existing theories on supplier relationships is following. The next section is describing the methodology that was followed, in order for data to be gathered from two organizations that accepted to provide information for the particular subject. Furthermore, within the next sections, the research findings are presented and analyzed. Finally, conclusions are drawn and recommendations for further research are made. Within the literature review section many themes and theories are described. This section starts with a description on how recent buyer-supplier relationships have been formed. Another description of the factors that are creating successful buyer-supplier relationships is following the previous part. In addition, how collaboration between small and large firms can be successfully discussed. Furthermore, the importance of trust and how it can be formed in buyer-supplier relationships is also mentioned. Finally, buyer-supplier mutual action, investments in supplier networks, potential risks of those investments and how those risks can be managed appropriately are also discussed. Within the Research Methodology section, the research approach and the research methods chosen (questionnaire and semi-structured interview) are discussed. In addition how the companies that were investigated were chosen, how the questions asked were designed and the limitations of the methodology are also evaluated. The next section is called Research Findings. Within this section the answers of the two organizations investigated (a large aircraft manufacturer and a medium chemical supplier) are presented. Those findings are also analyzed within the next section of the report, and important conclusions are made. Those conclusions were drawn based on research findings and on existing literature. The most important are: 1. Trust is the most important element in small supplier-large buyer relationship 2. Large organizations are willing to provide financial help to small supplier 3. A small supplier is willing to make high asset specific investments 4. Small suppliers are having more risks than the large buyers, if they enter in a partnership 5. An effective crisis management strategy needs to be developed. Those conclusions answered most of the initial research questions. However, there is still room for further research. Recommendations for further research are made within the last part of this report.